Accounting Conservatism and Its Implications - Suwarno Suwarno (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Introduction/Main Objectives: This research aims to reveal trends in the concept of accounting conservatism through a systematic literature review. Background Problems: Studies on the topic of accounting conservatism are very diverse with inconsistent study results and only a few have conducted research using a systematic literature review approach. Research Methods: This research uses a systematic literature review approach with a description analysis of 208 articles sourced from the Scopus database for 2005-2024 and processed with Bibliometrix R and VOSviewer. Finding/Results: The research findings reveal topic trends related to accounting conservatism, including corporate governance, financial reporting quality, information asymmetry, corporate social responsibility, and IFRS. Conclusion: This research outlines various research directions related to accounting conservatism, such as manager characteristics, economic and cultural conditions, and tax aggressiveness